The capabilities and human rights of high performance athletes. (March 2020) - Adams, Andrew; Kavanagh, Emma
High performance athletes participate and function in sports systems where exploitative behaviours may become manifest. These behaviours potentially violate an individual athlete's human rights. Using the Capability Approach first outlined by Amartya Sen the paper details how a more precise analysis of human rights, in the context of high performance sport, may be achieved. Using in-depth narrative accounts from high performance athletes, data illustrate how athlete maltreatment is related to individual capabilities and functionings: the loss of individual freedoms infringes accepted notions of human rights. The implications for practice concern how human rights may be protected within and for systems of high performance production.